Carboxylated graphene oxide nanosheets as efficient electrodes for high-performance supercapacitors - Abdu, Hassan Idris; Hamouda, Hamouda Adam; Orege, Joshua Iseoluwa; Ibrahim, Mohammed Hassan; Ramadan, Anas; Aboudou, Taslim; Zhang, Hongxia; Pei, Jinjin (Frontiers in Chemistry, 2022)
In the presence of dry ice, a series of graphitic materials with carboxylated edges (ECGs) were synthesized by ball milling graphite for varied times (24, 36, and 46 hours). The influence of carboxylation on the physiochemical characteristics and electrochemical performance as effective electrodes for supercapacitors were assessed and compared with pure graphite. Several characterization techniques were employed to investigate into the morphology, texture, microstructure, and modification of the materials. Due to its interconnected micro-mesoporous carbon network, which is vital for fast charge-discharge at high current densities, storing static charges, facilitating electrolyte transport and diffusion, and having excellent rate performance, the ECG-46 electrode among the investigated samples achieved the highest specific capacitance of 223 F g-1 at 0.25 A g-1 current density and an outstanding cycle stability, with capacitance retention of 90.8 % for up to 10,000 cycles. Furthermore, the symmetric supercapacitor device based on the ECG-46 showed a high energy density of 19.20 W h kg-1 at 450.00 W kg-1 power density. With these unique features, ball milling of graphitic material in dry ice represents a promising approach to realize porous graphitic material with oxygen functionalities as active electrodes.